RELEVANSI PRESIDENTIAL THRESHOLD DENGAN PRINSIP KEDAULATAN RAKYAT - Desmon, Andi (Soumatera Law Review, 2018)
As a means of implementing popular sovereignty, general elections have become a sort of agenda for modern state routines within a certain period of time to distribute power. Constitutionally, the implementation of general elections has been regulated in the 1945 Constitution of the Republic of Indonesia. The Presidential threshold is the concept of proposing presidential and vice presidential candidates. This proposal is carried out by political parties or joint political parties in election elections. Political parties or joint political parties are responsible for the proposed pair of presidents and vice presidents. This paper uses normative juridical research. General elections are the implementation of the principle of popular sovereignty. One of the principles of popular sovereignty is the recognition of the majority of the voice of sovereignty and giving respect to the voice of minorities by providing equal opportunities and benefits to achieve equality and justice. Therefore the implementation of the presidential threshold is not relevant to the principle of popular sovereignty, because it does not give respect to political parties that get a minority vote by providing equal opportunities and benefits to achieve equality and justice.